Best duration of dual antiplatelet therapy after drug-eluting stent implantation: an updated network meta-analysis of randomized controlled trials. Issue 1 (2nd January 2019) - Barbarawi, Mahmoud; Kheiri, Babikir; Zayed, Yazan; Aburahma, Ahmed; Osman, Mohammed; Barbarawi, Owais; Hicks, Michael; Hassan, Mustafa; Alkotob, Mohammad L.; Bachuwa, Ghassan
ABSTRACT: Background : Drug-eluting stent(DES) implantation is the main interventional treatment for coronary artery disease, and dual antiplatelet therapy(DAPT) remains the gold standard strategy to prevent ischemic events. However, the optimal duration of DAPT after DES implantation remains controversial. Therefore, we aimed to evaluate the best duration of DAPT following DES implantation. Method : We searched PubMed, Embase, Cochrane Library, and clinicaltrials.gov for all randomized clinical trials(RCTs) that compared different durations of DAPT after DES implantation. Major adverse cardiac events(MACE) and major bleeding were the primary and secondary outcomes, respectively. Results : We included 16 RCTs (n = 42, 993). The mean age of included patients was 63.1 ± 10.1. The primary outcome was statistically significant for lower MACE in patients who received DAPT for 24–48 months (mo) following DES when compared with those who received 3–6 mo of DAPT (odds ratio [OR] 0.75; 95% credible interval [CI] 0.58–0.97). There was nonstatistically significant difference in MACE when comparing those who received 12 mo of DAPT to those taking either 3–6 mo of DAPT (OR 0.86; 95% CI 0.69–1.08) or 24–48 mo of DAPT (OR 0.87; 95% CI 0.72–1.05). In contrast, major bleeding was significantly lower in those who received 3–6 mo of DAPT (OR 0.32; 95% CI 0.17–0.54) and 12 mo of DAPT (OR 0.43; 95% CI 0.27–0.63) than in those who received 24–48 mo of DAPT. Conclusion : In patients who undergo DES implantation, a longer duration of DAPT is associated with lower MACE, despite the increased risk of major bleeding events. Therefore, individualizing the duration of DAPT after DES according to the patient's risk of bleeding and recurrent ischemia is recommended.